Hadith:”My Father and Your Father are in Hellfire” A Theoretical and Applied Study according to the Principles of Hadith Criticism and Evaluation “al-Jarh and al-Ta’dil” - Hmed, Asma Taha; Shaaban, Mohammed J. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The science of al-Jarh and al-Ta’dil has a lofty status and a high rank among the sciences of Shari’ah, as it is based on solid scientific foundations and objective controls. It is a science that deals with the men who transmit the hadith of the Prophet (peace be upon him), the relics and the news, and looking into the conditions of their acceptance and the reasons for their rejection, so that what is accepted is accepted, and what has one or more reasons for rejection is rejected. The importance of the science of jarh and ta’dīdīq is that it regulates the correctness of the hadīth from the weak, and that the first thing that must be done in jarh and ta’dīq is to collect all the narratives from the books of the Sunnah, so that some of them can be inferred. It turns out that the study of these methods together represents an integrated picture of understanding the hadith, taking into account the general from the specific, the restricted from the absolute, and the knowledge of the mansukh and nasuk. The theoretical aspect of the study focused on the theoretical foundations of the science of jarh and ta’deeq, and the applied aspect was useful in studying the hadith (My father and your father are in the fire) in terms of understanding the hadith and deflecting suspicions of what offends the Prophet’s honor. The research came in an introduction, two research topics, and a conclusion with findings and recommendations. The introduction included the research objectives, the research question, the research methodology, the methodology, and the research plan.